2017
DOI: 10.1002/ppsc.201600428
|View full text |Cite
|
Sign up to set email alerts
|

Multilayered Materials Comprising Mesoporous Thin Films and Metal Nanoparticles

Abstract: The ORCID identification number(s) for the author(s) of this article can be found under http://dx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 62 publications
1
7
0
Order By: Relevance
“…Furthermore, from these images it can be concluded that the mesoporous thin film formation was not affected by the roughness of the substrate imposed by the immobilized NPs. 49 Similar results were obtained for Au15dY/TF and Au35dY/TF systems ( Figures S2 and S3, respectively).…”
Section: Resultssupporting
confidence: 84%
“…Furthermore, from these images it can be concluded that the mesoporous thin film formation was not affected by the roughness of the substrate imposed by the immobilized NPs. 49 Similar results were obtained for Au15dY/TF and Au35dY/TF systems ( Figures S2 and S3, respectively).…”
Section: Resultssupporting
confidence: 84%
“…These results are in agreement with those previously obtained for silica films and multilayered systems. 27,44 Regarding the film thicknesses, they are still in the same range (180-200 nm, Table S5 and Figure S6), although some differences are observed due to the fact that spin coating was used to prepare Au66/TX samples, instead of dip coating procedure used for TX samples. Moreover, the films are smooth over the Au NPs (Figure S6).…”
Section: Overgrowth Of Au Nps Placed Below Mesoporous Tio 2 Thin Filmmentioning
confidence: 97%
“…Thus, samples were treated at 200 °C to consolidate the oxide, followed by ethanol extraction of the template, a procedure that was previously used for MOTFs or composites that contain other thermally sensitive chemical moieties or particles [9a,b,d,13] . Only if following this treatment, we conserved the UCNPs' emission and obtained smooth and transparent thin films composites.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it is possible to conclude that the presence of the UCNPs does not significantly affect neither the porosity nor the mesoporous structure of the oxide thin films. The UCNPs can be considered as another combinable building block for developing composite thin films, likewise metallic and/or SiO 2 nanoparticles [9a,d] …”
Section: Resultsmentioning
confidence: 99%